PROJECT MANAGEMENT ASSESSMENT AND IMPLEMENTATION PLAN IN CONSTRUCTION ENGINEERING CONSULTANCY COMPANY (CASE STUDY: PT PETRA PENIDA ENERGI - Christovel, Delano
PT Petra Penida Energi Indonesia is a construction engineering consultancy company. In carrying out the project, timely completion of the project and within the budget are two important things that must be maintained. In the 2018-2020 period, there were 21 projects that experienced issues that made them delayed and over budget. For this reason, it is necessary to conduct research to find out what are the main factors that influence the delayed completion time and over budget, and to provide recommendations to prevent project delayed and over budget.